Are nucleosome positions in vivo primarily determined by histone–DNA sequence preferences? - Stein, Arnold (Oxford University Press, 2010)
Large-scale and genome-wide studies have concluded that ∼80% of the yeast (Saccharomyces cerevisiae) genome is occupied by positioned nucleosomes. In vivo this nucleosome organization can result from a variety of mechanisms, including the intrinsic DNA sequence preferences for wrapping the DNA around the histone core. Recently, a genome-wide study was reported using massively parallel sequencing to directly compare in vivo and in vitro nucleosome positions. It was concluded that intrinsic DNA sequence preferences indeed have a dominant role in determining the in vivo nucleosome organization of the genome, consistent with a genomic code for nucleosome positioning. Some other studies disagree with this view. Using the large amount of data now available from several sources, we have attempted to clarify a fundamental question concerning the packaging of genomic DNA: to what extent are nucleosome positions in vivo determined by histone-DNA sequence preferences? We have analyzed data obtained from different laboratories in the same way, and have directly compared these data. We also identify possible problems with some of the experimental designs used and with the data analysis. Our findings suggest that DNA sequence preferences have only small effects on the positioning of individual nucleosomes throughout the genome in vivo.